The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1098/rsos.150702
|View full text |Cite
|
Sign up to set email alerts
|

Microelastic mapping of the rat dentate gyrus

Abstract: The lineage commitment of many cultured stem cells, including adult neural stem cells (NSCs), is strongly sensitive to the stiffness of the underlying extracellular matrix. However, it remains unclear how well the stiffness ranges explored in culture align with the microscale stiffness values stem cells actually encounter within their endogenous tissue niches. To address this question in the context of hippocampal NSCs, we used atomic force microscopy to spatially map the microscale elastic modulus (E) of spec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 30 publications
0
18
2
Order By: Relevance
“…However, our findings are in contrast with previous studies, which found a positive correlation between stiffness and cell nucleus area on the spinal cord of the adult mouse, retina of the ruminant and embryonic brain of Xenopus [3,30,32]. Furthermore, granular cell layer in coronal hippocampal slices of the juvenile rats was also shown to be stiffer than hilus [21]. While different CNS tissue composition might be the reason for the discrepancy between our results and those reported in the literature, it is worth stressing that our indentation protocol significantly differs with respect to that used in previous studies.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…However, our findings are in contrast with previous studies, which found a positive correlation between stiffness and cell nucleus area on the spinal cord of the adult mouse, retina of the ruminant and embryonic brain of Xenopus [3,30,32]. Furthermore, granular cell layer in coronal hippocampal slices of the juvenile rats was also shown to be stiffer than hilus [21]. While different CNS tissue composition might be the reason for the discrepancy between our results and those reported in the literature, it is worth stressing that our indentation protocol significantly differs with respect to that used in previous studies.…”
Section: Discussioncontrasting
confidence: 99%
“…It is therefore commonly agreed that a deep knowledge of the correlation between brain composition and mechanical properties of the tissue would enable neuroscientists to shed light on how mechanotransduction phenomena contribute to the functioning of the brain. Furthermore, a quantitative assessment of the viscoelasticity characteristics of the different regions of the brain could pave the way for the improvement of computational brain injury models [15], the engineering of brain phantoms for surgical practise [16,17], the design of mechanically matched brain implants [18], and the production of soft substrates that could mimic different mechanical environments for investigations of stiffness-dependent neural stem cell differentiation [19][20][21] and neuronal and glial cell morphology [22]. Yet, at present, the relation between mechanical properties and cytoarchitecture is still largely unknown.…”
mentioning
confidence: 99%
“…For example, some of the studies used tips with the radius of 250 µm resulting in contact area much larger than individual anatomical regions of hippocampus and thus measuring averaged mechanical properties over multiple layers [16,17,18,19,25,26,27,22,44]. Other studies used smaller tips and indentation depths (R < 20 µm, h < 4 µm [28,45,46]), where reported relative differences between regions do not agree with our findings.…”
Section: Viscoelastic Mapping Of Hippocampus and Cerebellumcontrasting
confidence: 76%
“…To examine the impact of stiffness on NSC behavior, the Schaffer and Healy laboratories developed synthetic hydrogel culture systems with variable elastic moduli and found that modulus strongly influences neuronal vs. astrocytic differentiation of adult hippocampal NSCs, with softer gels favoring neurons and harder gels promoting astrocytes (Saha et al 2008). In addition, the hippocampal NSC niche has local stiffness gradients (Luque et al 2016). Though changes in brain stiffness have been attributed to pathology associated with neurodegeneration, cancer, and acute injuries that cause glial scarring, the reported research on brain stiffness parameters in elderly individuals is more limited, with most age-related studies focusing on early development versus young adult brains.…”
Section: Extracellular Matrix Signalsmentioning
confidence: 99%